Metabolic Risk Factors Associated With Chronic Kidney Disease in a Middle-Aged and Elderly Taiwanese Population: A Cross-Sectional Study - Lu, Mei-Chun; Chen, I-Ju; Hsu, Le-Tien; Chen, Ying-Jen; Tsou, Meng-Ting; Tung, Tao-Hsin; Chen, Jau-Yuan (Frontiers in Medicine, 2021)
Background: This study aimed to quantify the proportion of participants with chronic kidney disease (CKD) and associated metabolic risk factors in a middle-aged and elderly population in Guishan District, Taoyuan City, Taiwan. Methods: This cross-sectional study enrolled residents aged 50–90 years living in one community. All participants received a standardized personal interview, including a structured questionnaire, anthropometric measurements, and blood samples collected for laboratory testing. CKD was defined as the presence of kidney damage (urine albumin-creatinine ratio ≥30 mg/g) or estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m2. Multiple logistic regression models were used to evaluate the risk factors associated with CKD. Results: A total of 400 participants were enrolled. The overall proportion of participants with CKD was 20.5% (95% confidence interval [CI]: 16.54–24.46%). The proportions of participants with CKD among those aged 50–64 years, 65–74 years, and 75 years and over were 17.7%, 18.8%, and 35.7%, respectively (p = 0.01). Multiple logistic regression model revealed that elevated blood pressure (odds ratio [OR] =2.23, 95% CI: 1.16–4.30), hyperglycemia (OR =2.87, 95% CI: 1.64–5.00), hyperuricemia (OR =1.38, 95% CI: 1.14–1.69), and metabolic syndrome (OR =2.30, 95% CI: 1.31–4.06) were significantly associated with CKD. Conclusions: The prevalence of CKD in the study population was high. Hypertension, hyperglycemia, hyperuricemia, and metabolic syndrome are significantly associated with CKD in a middle-aged and elderly population in Taiwan.